2022
DOI: 10.24072/pcjournal.190
|View full text |Cite
|
Sign up to set email alerts
|

Divergence of olfactory receptors associated with the evolution of assortative mating and reproductive isolation in mice

Abstract: Deciphering the genetic bases of behavioural traits is essential to understanding how they evolve and contribute to adaptation and biological diversification, but it remains a substantial challenge, especially for behavioural traits with polygenic architectures. In this study, we developed a population genomics approach coupled with functional predictions to address the evolution and genetic basis of olfactory-based assortative mate preferences in the house mouse, suspected to have evolved as a response to sel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 132 publications
0
7
0
Order By: Relevance
“…3C and reviewed by Servedio and Noor 2003;Hopkins 2013;Butlin and Smadja 2018). However, studies investigating LD between post-and prezygotic barrier loci and the effect of indirect reinforcing selection on prezygotic barrier loci in a reinforcement scenario remain rare (but see in Phlox, Hopkins and Rausher 2012 or house mice, Smadja et al 2022). Interesting parallels occur in the context of spatial clines, where enhancement of LD among barrier loci may evolve in response to indirect selection.…”
Section: Deterministic and Incidental Factors Favoring The Build-up O...mentioning
confidence: 99%
See 1 more Smart Citation
“…3C and reviewed by Servedio and Noor 2003;Hopkins 2013;Butlin and Smadja 2018). However, studies investigating LD between post-and prezygotic barrier loci and the effect of indirect reinforcing selection on prezygotic barrier loci in a reinforcement scenario remain rare (but see in Phlox, Hopkins and Rausher 2012 or house mice, Smadja et al 2022). Interesting parallels occur in the context of spatial clines, where enhancement of LD among barrier loci may evolve in response to indirect selection.…”
Section: Deterministic and Incidental Factors Favoring The Build-up O...mentioning
confidence: 99%
“…Finally, tight linkage is also found among loci underlying a single barrier trait (local adaptation: e.g., Roda et al 2017; mating signal: e.g. Heliconius: Byers et al 2021; Laupala crickets Xu and Shaw 2021; mate preferences: house mice: Smadja et al 2022;pollinator syndrome: Petunia: Hermann et al 2013), suggesting that coupling at this level might also be important to consider. QTL for multiple barrier traits map to inversions in some taxa, such as Mimulus (Lowry and Willis 2010), Helianthus (Huang et al 2020) and Littorina (Koch et al 2022) (see also Berdan et al,…”
Section: The Role Of Recombination and Genetic Architectures: Enhance...mentioning
confidence: 99%
“…Custom scripts were used to format filtered sync files into BAYPASS input files (Smadja et al 2022b). We run BAYPASS separately for the autosomes and the X chromosome and specified the pool haploid sample sizes to activate the Pool-Seq mode of BAYPASS.…”
Section: Population Contrasts and Baypass Proceduresmentioning
confidence: 99%
“…Since we had no a priori knowledge of the genetic architecture of our phenotype of interest (mate preference), nor on which one of the test statistics was optimal for our analysis, we used those two different statistics and reported as outlier genes those showing significant C2_max or C2_mean statistics. The significance of each gene-based differentiation statistic was assessed using custom permutation procedures (Smadja et al 2022b). C2_max estimates are influenced by the nucleotide diversity of each gene: the larger the number of SNPs it contains, the more likely are extreme C2_max values.…”
Section: Identification Of Outlier Genesmentioning
confidence: 99%
“…Positive assortative mating (hereafter, assortative mating), wherein genotypic or phenotypic trait values are positively correlated between mates, has been empirically observed across animal species ( Jiang et al 2013 ). Theoretical and empirical studies have demonstrated the consequences of assortative mating for speciation and hybridization ( Kondrashov 1983 ; Otto et al 2008 ; Tung et al 2012 ; Schumer et al 2017 ; Kopp et al 2018 ; Powell et al 2021 ; Muralidhar et al 2022 ; Natola et al 2022 ; Smadja et al 2022 ; Robinson et al 2023 ), and for the distributions of traits within populations ( Wright 1921 ; Norris et al 2019 ; Kim et al 2021 ; Border et al 2022 ; Muralidhar et al 2022 ; Horwitz et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%